Access 2003 personal trainer - O'Reilly. (Beijing : O'Reilly, 2005)
This straightforward, practical, and complete guide to mastering the powerful and complex OpenBSD operating system, is for the experienced UNIX user who wants to add OpenBSD to his or her repertoire. The author assumes a knowledge of basic UNIX commands, design, and permissions. The book takes you through the intricacies of the platform and teaches how to manage your system, offering friendly explanations, background information, troubleshooting suggestions, and copious examples throughout.
Includes index.
Keywords: Database management; Microsoft Access